Comparison of traditional anesthesia method and jet injector anesthesia method (MadaJet XL®) for Nexplanon® insertion and removal - G. Anthony Wilson; Julie W. Jeter; William S. Dabbs; Amy Barger Stevens; Robert E. Heidel; Shaunta' M. Chamberlin (BMC, 2020)
Abstract Background This study compared a needle-free anesthesia method with traditional local anesthesia for insertion and removal of Nexplanon® long-acting removable contraceptive device. In our clinic, patients often avoid this highly effective form of contraception due to fear of needles. We sought to determine if patients perceived a difference in pain with the injection, anxiety level or pain with the procedure when local anesthesia was given with a needle v/s a needle-free jet injector device. Methods Patients were randomly assigned to one of two groups: jet injector or needle lidocaine delivery. Outcomes were ease of use, patient anxiety level, painfulness, and efficacy of anesthesia method. Results Patient pain perception with administration of jet injector lidocaine was statistically lower than traditional needle with no difference in anxiety or ease of use, or efficacy of the anesthesia. Conclusion The jet injector device is a reasonable alternative to needle injection delivery of anesthesia prior to insertion/removal of Nexplanon® device. Further studies may determine whether this needle-free alternative for administration of local anesthetic would result in more women choosing Nexplanon® as a contraceptive method.